An empirical relationship between PM2.5 and aerosol optical depth from MODIS satellite images for spatial simulation over Ho Chi Minh city - Vo Quoc Bao; Tran Thi Van (Vietnam Journal of Science, Technology and Engineering, 2021)
Air quality in megacities has been a pressing concern of environmental managers and scientists for decades. Indeed, particulate matter (PM), especially PM2.5, is considered a dangerous particle that is harmful to human health. The current sparse monitoring network in Ho Chi Minh city (HCMC) does not accurately reflect the spatial distribution of fine particles in ambient air. Therefore, this research examines the relationship between ground-based station data and aerosol optical depth (AOD) imagery from the Moderate Resolution Imaging Spectroradiometer (MODIS) onboard the Terra/Aqua satellite to establish a PM2.5 distribution map of HCMC. PM2.5 concentration values monitored from two ground stations were collocated by time and space with Terra/MODIS AOD data from the period of 2016-2020. Pairs of values were checked for correlation and then fit to several regression functions. The most suitable function was chosen to simulate the quantified PM2.5 distributions in the study area. A high correlation between PM2.5 concentrations and AOD at the wavelength of green light (R2=0.810) was found with a linear regression model. The results showed that the highest concentration of PM2.5 was in February, and the mean value was higher than QCVN 05:2013 (32.5 µg/m3 compared with 25 µg/m3, annual mean). These results support the need for essential air quality monitoring in HCMC.